Fabrication and characterisation of highly aligned fibrous assemblies / Tan Chin Joo - Tan , Chin Joo (2020)
Vascular grafting has been an effective remedy to vascular diseases for decades. Autografting by using the veins or arteries in the patient’s body is found to have patency rate for years. However, autografting may not be possible when compatible vessels are not available. In this case, synthetic vascular grafts are found to be effective replacements. Nevertheless, synthetic grafts with diameter less than 4 mm becomes challenging due to thrombogenicity and mismatch of mechanical properties with the native vessels. Along this line, the ability to develop new biostable synthetic materials suitable for smaller grafts and the ability to evaluate their resulting mechanical properties in view of minimizing properties mismatch become essential. The present thesis can be regarded as a first step toward integrated design of new biostable synthetic materials suitable for small diameter vascular grafts, i.e. less than 4 mm. While biological considerations are equally important, the emphasis of the present work is laid on the fabrication and evaluation of mechanical properties of materials using both experimental and numerical works. Owing to its wide use in biomedical applications, thermoplastic polyurethane elastomer is considered. To this end, the first stage of the work consists in fabricating single layer highly aligned thermoplastic polyurethane fibrous assemblies using dry spinning technique assisted by a weak electrical field. Simple biostability characterizations are conducted on the fibrous samples after immersing them in simulated body fluid for 24 weeks. Results indicate that the polyurethane fibres show no observable or significant deteriorations in physical, mechanical and chemical properties. The second stage of the work deals with the mechanical responses of single and multilayer highly aligned fibrous assemblies. The multilayer assemblies are obtained by weaving two single layer highly aligned assemblies at various woven angles during the spinning: 0°, 16° and 26°. Tensile samples are extracted from these assemblies and subjected to a number of mechanical tests. Results show that single layer assemblies are strongly anisotropic and exhibit inelastic mechanical responses along fibre direction such as hysteresis, stress-softening, stress relaxation and residual strain. For multilayer woven assemblies with average fibre’s diameters of approximately 8 and 15 μm, the dependences of effective elastic modulus on woven angle and fibre average diameter are investigated. The last stage of the work consists in evaluating the applicability of the classical linear elastic laminate theory to multilayer fibrous assemblies in view of predicting their elastic properties. The final aim is to propose new designs of vascular graft consisting of multilayer highly aligned fibrous assemblies whose mechanical properties match with those of native vessels. Results predicted using the classical laminate theory show that the polyurethane fibrous assemblies with fibres diameter approximately 8 μm, woven angle close to 100o and thickness ranges between 0.5 to 0.7 mm could be suitable as the grafts of carotid arteries.